High-strong-ductile magnesium alloys by interactions of nanoscale quasi-long period stacking order unit with twin - Lutong Zhou; Tingting Niu; Guodong Zou; Huhu Su; Suyun He; Shijian Zheng; Yulong Zhu; Peng Chen; Carlos Fernandez; Qiuming Peng (Journal of Magnesium and Alloys)
Magnesium alloys with high strength in combination of good ductility are especially desirable for applications in transportation, aerospace and bio-implants owing to their high stiffness, abundant raw materials, and environmental friendliness. However, the majority of traditional strengthening approaches including grain refining and precipitate strengthening can usually prohibit dislocation movement at the expense of ductility invariably. Herein, we report an effective strategy for simultaneously enhancing yield strength (205 MPa, 2.41 times) and elongation (23%, 1.54 times) in a Mg-0.2Zn-0.6Y (at.%) alloy at room temperature, based on the formation of a nanosized quasi-long period stacking order unit (QLPSO)-twin structure by ultrahigh-pressure treatment followed by annealing. The formation reason and strong-ductile mechanism of the unique QLPSO-twin structure have been clarified by transmission electron microscopy observations and molecule dynamics simulations. The improved strength is mainly associated with the presence of nanosized QLPSO and the modified ∠86.3o QLPSO-twin boundary (TB) interface, effectively pinning dislocation movement. Comparatively, the enhanced ductility is related to the ∠3.7o QLPSO-TB interface and micro-kinks of nanoscale QLPSO, providing some paths for plastic deformation. This strategy on the QLPSO-twin structure might provide an alternative perspective for designing innovative hexagonal close-packed structural materials with superior mechanical properties.